2018
DOI: 10.1590/2175-8239-jbn-3931
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics in the treatment of chronic kidney disease: a systematic review

Abstract: Chronic kidney disease (CKD) is a syndrome caused by the progressive reduction of renal function. This study aimed to systematically examine the effects of supplementation with probiotics in the treatment of CKD. Searches were carried out on databases MEDLINE (PubMed), SciELO, Cochrane, and Clinical Trials. Two independent reviewers selected the studies from which data was extracted. The search included papers written in English and Portuguese published in the 2012-2016 period describing randomized clinical tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0
7

Year Published

2018
2018
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 27 publications
2
29
0
7
Order By: Relevance
“…12 Also, a mixture of Bidobacterium and Lactobacillus species could alleviate chronic kidney failure by reducing the plasma levels of urea, indoxyl sulfate and p-cresol. 13 More relevant to this study, probiotics were found to inhibit the development of colon cancers through inducing apoptosis and modulating the cellular defensive mechanisms. 14 Prebiotics are bioactive substances, fermented by the normal gut microora to benecial products such as butyrate and propionate which inhibit colon cancer biomarkers.…”
Section: Introductionmentioning
confidence: 92%
“…12 Also, a mixture of Bidobacterium and Lactobacillus species could alleviate chronic kidney failure by reducing the plasma levels of urea, indoxyl sulfate and p-cresol. 13 More relevant to this study, probiotics were found to inhibit the development of colon cancers through inducing apoptosis and modulating the cellular defensive mechanisms. 14 Prebiotics are bioactive substances, fermented by the normal gut microora to benecial products such as butyrate and propionate which inhibit colon cancer biomarkers.…”
Section: Introductionmentioning
confidence: 92%
“…According to the currently available evidence in a meta-analysis, there is no conclusive rationale for recommending biotic supplements for improving outcomes in renal patients [ 162 ]. Recent studies showed promising effects of probiotics in renal function and reduced levels of urea, blood urea nitrogen, and indoxyl sulfate in CKD patients [ 163 ]. Immunological, biochemical, and hemodynamic mechanisms are involved in the pathogenesis of AKI.…”
Section: Nutrients and Bioactive Compoundsmentioning
confidence: 99%
“…Chronic kidney disease (CKD) is a lethal global syndrome, also called “silent disease,” characterized by progressive reduction in renal functions, kidney infection commencement, and premature death. Incidence of diabetes mellitus, obesity, and hypertension largely contributed to the prevalence of CKD ( Fagundes et al, 2018 ). Wang et al (2015) reported prophylactic and therapeutic effects of Lactobacillus and Bifidobacterium spp.…”
Section: Health-boosting Spectrum Of Probioticsmentioning
confidence: 99%